Tumor acidosis enhances cytotoxic effects and autophagy inhibition by salinomycin on cancer cell lines and cancer stem cells - Pellegrini, Paola; Dyczynski, Matheus; Sbrana, Francesca Vittoria; Karlgren, Maria; Buoncervello, Maria; Hägg-Olofsson, Maria; Ma, Ran; Hartman, Johan; Bajalica-Lagercrantz, Svetlana; Grander, Dan; Kharaziha, Pedram; De Milito, Angelo (Oncotarget, 2016)
Sustained autophagy contributes to the metabolic adaptation of cancer cells to hypoxic and acidic microenvironments. Since cells in such environments are resistant to conventional cytotoxic drugs, inhibition of autophagy represents a promising therapeutic strategy in clinical oncology. We previously reported that the efficacy of hydroxychloroquine (HCQ), an autophagy inhibitor under clinical investigation is strongly impaired in acidic tumor environments, due to poor uptake of the drug, a phenomenon widely associated with drug resistance towards many weak bases. In this study we identified salinomycin (SAL) as a potent inhibitor of autophagy and cytotoxic agent effective on several cancer cell lines under conditions of transient and chronic acidosis. Since SAL has been reported to specifically target cancer-stem cells (CSC), we used an established model of breast CSC and CSC derived from breast cancer patients to examine whether this specificity may be associated with autophagy inhibition. We indeed found that CSC-like cells are more sensitive to autophagy inhibition compared to cells not expressing CSC markers. We also report that the ability of SAL to inhibit mammosphere formation from CSC-like cells was dramatically enhanced in acidic conditions. We propose that the development and use of clinically suitable SAL derivatives may result in improved autophagy inhibition in cancer cells and CSC in the acidic tumor microenvironment and lead to clinical benefits.